Direct duplication of the Y chromosome with normal phenotype – incidental finding in two cases. (18th June 2012) - Kuan, L.‐C.; Su, M.‐T.; Kuo, P.‐L.; Kuo, T.‐C.
Summary Structural rearrangement in the Y chromosome is closely involved in spermatogenesis. However, several Y chromosome variants may have no deleterious effects on male reproduction. Here, we report two cases of Y chromosomal duplication from incidental findings. Their FISH analysis revealed direct duplication of large segments of short and long arms of the Y chromosome. Nearly two intact Y chromosomes were carried in these two cases with normal phenotype.